Seasonality in Crete: Problem or a way of life? - Andriotis, Konstantinos (My University, 2005)
The tourism industry worldwide faces seasonal fluctuations of demand. These fluctuations are attributed to diverse factors - mainly climatic conditions, human decisions, inertia or tradition and supply restrictions - and result in various problems for tourist-receiving destinations, such as seasonal environmental congestion, low return on investment for tourist enterprises, overuse of facilities and off-season unemployment. Most of the strategies adopted by both private and public sectors to overcome seasonality fall into one of three main categories: diversification of the product mix, change of the customer mix and aggressive pricing. This paper reviews these issues taking the case of the island of Crete, and examines whether seasonality poses a problem for the island and the islanders or whether it is simply a way of life.
Keywords: Crete; Determinants; Seasonality; Strategies; Tourism